Systematic Study of Heteroarene Stacking Using a Congeneric Set of Molecular Glues for Procaspase-6 - Togo Takaya; Tram Linh; Denton Laura G.; ElHilali-Pollard Xochina; Gu Jun; Jiang Jinglei; Liu Chenglei; Zhao Yan; Zhao Yanlong; Zheng Yinzhe; Zheng Yunping; Yang Jingjing; et al. (AMER CHEMICAL SOC, 2025)
Heteroaromatic stacking interactions are important indrug binding,supramolecular chemistry, and materials science, making protein-ligandmodel systems of these interactions of considerable interest. Herewe studied 30 congeneric ligands that each present a distinct heteroarenefor stacking between tyrosine residues at the dimer interface of procaspase-6.Complex X-ray crystal structures of 10 analogs showed that stackinggeometries were well conserved, while high-accuracy computations showedthat heteroarene stacking energy was well correlated with predictedoverall ligand binding energies. Empirically determined K (D) values in this system thus provide a useful measureof heteroarene stacking with tyrosine. Stacking energies are discussedin the context of torsional strain, the number and positioning ofheteroatoms, tautomeric state, and coaxial orientation of heteroarenein the stack. Overall, this study provides an extensive data set ofempirical and high-level computed binding energies in a versatilenew protein-ligand system amenable to studies of other intermolecularinteractions.